158k views
4 votes
Determine the value of g(4), g(3 / 2), g (2c) and g(c+3) then simplify as much as possible.

g(r) = 2
\pi r h

User Andruso
by
5.9k points

2 Answers

6 votes

For this case we have the following function:


g (r) = 2 \pi * r * h

We must evaluate the function for different values:


g (4) = 2 \pi * (4) * h = 8 \pi*h\\g (\frac {3} {2}) = 2 \pi * (\frac {3} {2}) * h = 3 \pi*h\\g (2c) = 2 \pi * (2c) * h = 4 \pi * c * h\\g (c + 3) = 2 \pi * (c + 3) * h = 2 \pi * c * h + 6 \pi * h

Answer:


g (4) = 8 \pi*h\\g (\frac {3} {2}) =3 \pi*h\\g (2c) = 4 \pi * c * h\\g (c + 3) = 2 \pi * c * h + 6 \pi * h

User Ericharlow
by
5.4k points
2 votes

Answer:


g(4) = 8 \pi h\\\\g((3)/(2)) = 3 \pi h\\\\ g(2c) = 4 \pi ch\\\\g(c+3) = 2 \pi hc+6\pi h

Explanation:

You need to substitute
r=4 into
g(r) = 2 \pi r h. Then:


g(4) = 2 \pi(4)h\\\\g(4) = 8 \pi h

Substitute
r=(3)/(2) into
g(r) = 2 \pi r h. Then:


g((3)/(2)) = 2 \pi((3)/(2))h\\\\g((3)/(2)) = 3 \pi h

Substitute
r=2c into
g(r) = 2 \pi r h. Then:


g(2c) = 2 \pi(2c))h\\\\g(2c) = 4 \pi ch

Substitute
r=c+3 into
g(r) = 2 \pi r h. Then:


g(c+3) = 2 \pi (c+3)h\\\\g(c+3) = 2 \pi hc+6\pi h

User Chris Ritchie
by
5.4k points